Factors Influencing Ulcer Healing in Chronic Limb Threatening Ischemia Patients after Endovascular Angioplasty at Cipto Mangunkusumo General Hospital - Suhartono, Raden; Wijaya, Ghany H; Muradi, Akhmadu (The New Ropanasuri Journal of Surgery, 2023)
Introduction. Chronic limb–threatening ischemia (CLTI) can cause rest pain in the lower extremities and the formation of ulcers or gangrene. Revascularization, which can be done using open surgery or endovascular procedures, is the first line of treatment in CLTI management. CLTI patients at CMGH usually came with advanced conditions and high re–amputation rates even after revascularization. This study aimed to determine factors associated with the outcome of endovascular angioplasty, especially ulcer healing. Method. A cross–sectional study was conducted at CMGH, enrolling CLTI patients with Rutherford grades 5 and 6 who underwent angioplasty. Age, gender, history of smoking, hypertension, atrial fibrillation, heart failure, chronic kidney disease (CKD), and diabetes mellitus were the independent variables of interest in this study. The dependent variable was ulcer healing, a clinical assessment after angioplasty assessed as complete ulcer epithelialization within four months after the procedure. Results. In 133 study subjects, it was found that 60.9% of patients underwent complete epithelialization. Factors that affect ulcer healing in CLTI patients include gender, hypertension, atrial fibrillation, heart failure, chronic kidney disease, and diabetes mellitus. The factor with the strongest association with ulcer healing after endovascular angioplasty based on the logistic regression test is diabetes mellitus. Conclusion. Factors that have a significant association with ulcer healing in patients with CLTI include gender, smoking, hypertension, atrial fibrillation, heart failure, CKD, and diabetes. The factor that was considered to have the strongest association was diabetes mellitus